Diagnóstico y alternativas al sistema de gestión de residuos sólidos en dos parroquias del cantón Espindola pertenecientes a la cuenca alta del Rio Catamayo - Mora Ortega, Viviana Noemí (2020)
In this research, entitled “Diagnosis and alternatives to the waste management system In two parishes of canton Espindola which belong to the high basin of Catamayo river”. A diagnosis to the management system of solid waste took place in parishes Amaluza and Jimbura, Espindola canton. These areas present an environmental worrying situation due to the inadequate solid waste management. This is why, it is necessary to have a characterization of solid waste coming from different sources, such as, homes, shops, and special sources, determining the amount of waste generation from every source. In the characterization process, the following parameters considered were per capita generation, total daily generation, and waste density. After this, using observation, interview, and questioner techniques to the staff in charge of the Management, Protection and Environmental Unit of the Espindola Municipal GAD, to the president of Jimbura Parish Board, and to the inhabitants of Amaluza and Jimbura parishes, a base line is made in order to identify the present situation of solid waste management and the working state of the garbage dump of Espindola canton. From the information obtained, some alternatives were suggested in order to make an adequate management to the final arrangement of solid waste. The per capita production of Amaluza parish is 0,45 kg/inhabit/day with a total daily generation of 1547,10 kg/day; while Jimbura parish has a per capita production of 0,26 kg/inhabit/day with a total daily generation of 602,16 kg/day. The function of the alternatives suggested are to improve the solid waste management from its generation to its final arrangement. For this reason, the measures suggested are related to five different programs: environmental education, waste recovery and use, occupational security and health, improvement of the solid waste collection and transport, and restructuring of the garbage dump. The solid waste management will contribute to reduce the environmental impacts to natural resources (water, soil, and air), and improve the life quality of Espindola canton parishes population. Key words: Solid waste management, environmental quality, per capita generation.